Retrograde Endopyelotomy with Cutting Balloon™ for Treatment of Ureteropelvic Junction Obstruction in Infants - Parente, Alberto; Perez-Egido, Laura; Romero, Rosa Maria; Ortiz, Ruben; Burgos, Laura; Angulo, Jose Maria (Frontiers in Pediatrics, 2016)
Purpose The aim of this study is to analyze results of retrograde endopyelotomy with cutting-balloon for treatment of ureteropelvic junction obstruction (UPJO) in infants. Methods We routinely treat patients with UPJO under 18 months of age with retrograde high-pressure balloon dilatation of the pelviureteric junction (PUJ). During the procedure, in those cases where narrowing at the PUJ persists, endopyelotomy with cutting-balloon is performed. Endopyelotomy is performed over guidewire with 5 mm Cutting-Balloon™ under fluoroscopic control. Double-J stents is left in situ for 4 weeks. We retrospectively analyzed the postoperative, clinical and radiological outcome infants treated with cutting-balloon endopyelotomy between 2007-2015. Results Sixteen patients required cutting-balloon endopyelotomy to achieve complete resolution of narrowing of the waist observed during high-pressure balloon dilatation of the PUJ. Mean operative time was 35±21 minutes (mean ±SD) and hospital stay was less than 24 hours in all patients. Complete resolution of the narrowing at the PUJ under fluoroscopy was achieved in all cases, with no perioperative complications. One patient presented an urinary tract infection postoperatively (Clavien grade II). Preoperatively all cases had grade IV SFU hydronephrosis with parenchymal thining. During follow up, resolution of the hydronephrosis was observed in 11 patients (grade I SFU). In 4 infants, there was an improvement of the hydronephrosis (grade II SFU) and the renogram curve. In one case, an open pyeloplasty was required due to persistent hydronephrosis and obstructive curve. Conclusion We believe that endopyelotomy with cutting-balloon could be a valid and safe option in minimally invasive management of UPJO in infants.